Logging traces of entity states in distributed environments - Ng, Pei Wen. (2012)
Distributed virtual environments systems are used to allow multiple users to communicate and interact with each other through different networks of connected workstations in a shared virtual world. In recent years, due to the enormous growth of multiplayer games development in the entertainment industry, this type of systems has become increasingly popular.